2020
DOI: 10.3389/fpsyg.2020.578108
|View full text |Cite
|
Sign up to set email alerts
|

(How) Does Affect Influence the Formation of Habits in Exercise?

Abstract: Objectives: Habitually instigated exercise is thought to increase health behavior maintenance. Previous research has explored several aspects of habit formation. However, there is a lack of longitudinal research investigating affective determinants, especially post-exercise affective states. Therefore, the present study aimed to investigate (a) if behavior frequency will enhance automaticity, (b) if positive affect will enhance automaticity, and (c) if positive affect will moderate the relationship between beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 84 publications
(114 reference statements)
1
6
1
Order By: Relevance
“…Habit was not included in the presented analyses. But we found support for affective valence post-exercise as well as an increase in valence during exercise promoting the development of automaticity of the decision to attend an exercise class in a previous analysis ( Weyland et al, 2020 ). The possible indirect effect of affective valence on behavior via habit strength postulated by the PAAM should be tested in future studies.…”
Section: Discussionsupporting
confidence: 60%
“…Habit was not included in the presented analyses. But we found support for affective valence post-exercise as well as an increase in valence during exercise promoting the development of automaticity of the decision to attend an exercise class in a previous analysis ( Weyland et al, 2020 ). The possible indirect effect of affective valence on behavior via habit strength postulated by the PAAM should be tested in future studies.…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, while many adolescents start PA programs to improve their health and lose weight, the rate of dropouts is high [9]. Specifically, regarding the maintenance of PA, researchers emphasize the role of affective processes [10][11][12]. Notably, there is a large volume of studies describing the critical role of enjoyment in PA [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Although the efficacy of SIT under hypoxia in improving exercise capacity and health status has been well-documented in the existing literature, affective responses to this type of training strategy have not been examined. Affective responses (i.e., enjoyment, affect) are exercise-induced feelings that potentially associate with exercise automaticity (i.e., willingness to exercise) and future exercise adherence [7][8][9]. Despite that adverse affective responses could more likely appear in performing exercise with supramaximal intensity according to the dual-mode theory [10], recent reviews suggested that, in most cases, enjoyment responses to HIIT were similar compared to moderate intensity continuous trainings when performed in normoxia [11][12][13].…”
Section: Introductionmentioning
confidence: 99%